Studies of Nondefective Adenovirus 2-Simian Virus 40 Hybrid Viruses. VI. Characterization of the DNA from Five Nondefective Hybrid Viruses - Henry, Patrick H. (1973)
Certain biophysical characteristics of the DNA from each of the five nondefective adenovirus 2 (Ad2)-simian virus 40 (SV40) hybrid viruses (Ad2(+)ND(1), Ad2(+)ND(2), Ad2(+)ND(3), Ad2(+)ND(4), Ad2(+)ND(5)) have been determined. The guanine plus cytosine content varied from 55 to 57% and was not significantly different from that of nonhybrid Ad2 (56%), and the hybrid DNA molecules had mean molecular lengths which were similar to that of the standard, Ad2. The Ad2 and SV40 components of each hybrid were linked by alkali-resistant, presumably covalent bonds. The percentage of SV40 DNA in each hybrid virus was determined by hybridization with SV40 complementary RNA in a calibrated system. The results indicate that each hybrid virus DNA contains a different percentage of SV40 nucleotide sequences. The estimated size of the SV40 DNA component varies from 48,000 daltons for Ad2(+)ND(3) to 840,000 daltons for Ad2(+)ND(4), the latter being equivalent to between one-fourth and one-third of the SV40 genome.